Adsorption of lead from aqueous solution onto coir-pith activated carbon - Kumar P.; Rao R.; Chand S.; Kumar S.; Wasewar K.L.; Yoo C.K. (My University, 2025)
Adsorption of lead (Pb(II)) from aqueous solution using H2SO4-activated carbon developed from coir pith (CPAC) was studied. Batch experiments were performed to explain the effect of initial pH (pH0), contact time, adsorbent dose, and temperature on adsorption. A pH0 of 5.0, a dose of 1 g L -1 for adsorption at a concentration of Pb of 20mgL -1 were the optimal conditions. The adsorption of lead onto CPAC was found to be a gradual process and the quasi-equilibrium condition reached in 4 h. The adsorption followed pseudo-second-order kinetics and the adsorption equilibrium followed the Temkin isotherm. Thermodynamic parameters such as ΔG0, ΔH0, and ΔS0 were evaluated by applying the Arrhenius and Van't Hoff equations, and it was found that adsorption of Pb(II) on CPAC was spontaneous and endothermic. © 2013 Balaban Desalination Publications.